INTONATION PATTERNS AS PERSUASIVE TOOLS IN MOTIVATIONAL VIDEO SERIES OF PRINCE EA - Озарникова, М.В.; Бежина, В.В. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2021)
This article is devoted to the study of intonation patterns in motivational video series of Prince Ea as means of persuasion. The authors consider the role of intonation in his motivational speeches and the existence of patterns in them, with the use of which Prince Ea has give the opportunity to influence people.